Fertility and Family Labor Supply - Katrine M. Jakobsen; Thomas H. Jørgensen; Hamish Low (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2022)
We study the role of fertility adjustments for the labor market responsiveness of men and women. First, we use longitudinal Danish register data and tax reforms from 2009 to provide new empirical evidence on asymmetric fertility adjustments to tax changes of men and women. Second, we quantify the importance of these fertility adjustments for understanding the labor supply responsiveness of couples through a life-cycle model of family labor supply and fertility. Allowing fertility adjustments increases the labor supply responsiveness of women by 28%. These adjustments affect human capital accumulation and has permanent implications for the gender wage gap within couples.
Keywords: J22; J13; D15; H24; 330; Fertility; Labor supply; Human capital accumulation; Gender inequality; Tax reform; Life-Cycle